China's Green Lights Program: A review and assessment. (November 2017) - Guo, Fei; Pachauri, Shonali
Abstract: Lighting accounts for 10–13% of China's electricity consumption. Triggered by the nationwide power shortage of the mid-1990s, the Chinese government launched its Green Lights Program in 1996. Since then, this program has been continuously highlighted in the nation's 9th–12th Five-Year Plans (1996–2015). This paper presents a review and assessment of this program during the past two decades. Based on available data, the achievements along with the implementation of this program are assessed by examining a set of indicators of electricity savings, consumer savings, market penetration, product quality, and production capacity expansion. The success of this programs can be attributed to several factors: 1) strong and sustained government commitment; 2) prioritized policy focus by program stages; 3) extensive efforts on product quality control; 4) a close symbiosis of energy efficiency policies with industrial development policies; and 5) the implementation of various incentive schemes. Nonetheless, several challenges are evident that the program needs to address in its next phase. These include: 1) promoting the use of efficient lighting products in rural China; 2) emphasizing the overall efficacy of lighting fixtures rather than focusing only on bulb efficacy; and 3) promoting the healthy development of an emerging semiconductor lighting industry in the nation. Highlights: China's Green Lights Program are assessed by a set of indicators. The program prioritizes policy focuses by stages. The success of the program can be attributed to five key factors. The program forms a symbiosis of energy efficiency policies with industrial policies. Several challenges are evident that the program needs to address in its next phase.